EXPLORING THE RENAISSANCE IN ORIENTAL LITERATURE - F. f.n. Turdiyeva N.Y Kahharova Mehriniso Kahramonovna Graduate student of the Samarkand State Institute of Foreign Languages (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
Oriental Renaissance, Alisher Navoi, Timurid Renaissance, Multiple Renaissances, cultural exchange, eurocentrism, human potential. Annotation: This article challenges the Eurocentric view of Renaissance by exploring the concept of "Oriental Renaissance" in literature. It examines potential candidates like the Timurid Renaissance, focusing on the figure of Alisher Navoi to highlight shared themes and divergences between Eastern and Western cultural revivals. The article argues for a more nuanced understanding of "Renaissance" and suggests alternative terms like "cultural revival" or "golden age."